2006
DOI: 10.1111/j.1567-1364.2006.00075.x
|View full text |Cite
|
Sign up to set email alerts
|

Yeast diversity sampling on the San Juan Islands reveals no evidence for the spread of the Vancouver IslandCryptococcus gattiioutbreak to this locale

Abstract: Biological diversity has been estimated for various phyla of life, such as insects and mammals, but in the microbe world is has been difficult to determine species richness and abundance. Here we describe a study of species diversity of fungi with a yeast-like colony morphology from the San Juan Islands, a group of islands that lies southeast of Vancouver Island, Canada. Our sampling revealed that the San Juan archipelago biosphere contains a diverse range of such fungi predominantly belonging to the Basidiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 23 publications
0
21
1
Order By: Relevance
“…on March 22, 2019 by guest http://aem.asm.org/ 092B/06), which were sampled by another group (21). These results suggest that there are "hot spots" of C. gattii within the sampled areas.…”
Section: Vol 73 2007 Environmental Cryptococcus Gattii In British Cmentioning
confidence: 79%
See 2 more Smart Citations
“…on March 22, 2019 by guest http://aem.asm.org/ 092B/06), which were sampled by another group (21). These results suggest that there are "hot spots" of C. gattii within the sampled areas.…”
Section: Vol 73 2007 Environmental Cryptococcus Gattii In British Cmentioning
confidence: 79%
“…It has been suggested that eucalyptus tree imports could be the route of introduction of C. gattii into the Pacific Northwest (20,21), particularly since one isolate (CBS7750) with a geno- (6,7,10,16,28,46,50,51). However, few of these studies have tested the hypotheses with genotypic data, and given the apparent global dispersal of C. gattii (31), it is difficult to demonstrate that C. gattii was absent from these areas prior to its isolation from imported trees.…”
Section: Vol 73 2007 Environmental Cryptococcus Gattii In British Cmentioning
confidence: 99%
See 1 more Smart Citation
“…gattii was consistently isolated from some areas. However, it was not found in the environment in other areas, such as the San Juan Islands ( 36 ), which suggests that environmental hot spots (zones of high concentration) of C . gattii may be found within the same broad ecologic niches.…”
Section: Ecologic Considerationsmentioning
confidence: 94%
“…Furthermore, the recovery rate of Cryptococcus spp. may be very low, thereby requiring a large number of samples to be taken without any guarantee of success [13]. …”
Section: Introductionmentioning
confidence: 99%